The Governance of Public Budgeting: a Proposal for Comparative Analyses - the Cases of São Paulo and London - Peres,Ursula Dias (2022)
This paper aims at understanding the governance of public budgeting in large metropolises with the use of comparative analysis. The analysis is focused on budgetary governance in London and São Paulo and uses qualitative and quantitative data from 2008 to 2019 to understand whether analytical categories such as incrementalism of expenditures, complexity of budgetary rules, bureaucratic hierarchy, bargaining, and muddling through are useful to compare two metropolises, especially to determine the discretionary power of mayors in making budget allocation decisions. The analytical categories are derived from the studies of theorists of economics and political sociology, notably Wildavsky (1975, 1969), Wildavsky and Caiden (2004), Schick (2009, 1976), Caiden (2010) Lascoumes and Le Galès (2005), Baumgartner and Jones (2005), and Fuchs (2012, 2010). The main argument of the paper is that, despite the administrative and political differences between London and São Paulo, similar dimensions can explain decisions about budget allocation and the political discretionary power of mayors. The study shows that mayors have little discretionary power, particularly in contexts of fiscal austerity; it also highlights the importance of property tax as a means to protect such power.